Cyberspace and national security in Malaysia - Malek Farok, Ainaa Nadzirah; Hossain, Ishtiaq (IIUM Press, International Islamic University Malaysia, 2017)
This book discusses the linkages between cyberspace and national security in Malaysia. It also discusses the views of government personnel as well as those from private agencies about the relationship between cyberspace and national security of the country. The book examines the nature of threats to cyberspace in public and private sectors in Malaysia, and also analyses the policies adopted by the Malaysian government to deal with cyber threats in Malaysia. The book uses both primary and secondary sources. It uses data collected from online interviews conducted with a number of personnel working in public and private agencies in Malaysia. Data were also collected from such primary sources as official reports, publications and various documents on the subject published by Cyber Security Malaysia, Bank Negara Malaysia, and the Malaysian Communications and Multimedia Commission.